2012
DOI: 10.1038/emboj.2012.16
|View full text |Cite
|
Sign up to set email alerts
|

Reversible phosphocholination of Rab proteins byLegionella pneumophilaeffector proteins

Abstract: The Legionella pneumophila protein AnkX that is injected into infected cells by a Type IV secretion system transfers a phosphocholine group from CDP-choline to a serine in the Rab1 and Rab35 GTPase Switch II regions. We show here that the consequences of phosphocholination on the interaction of Rab1/Rab35 with various partner proteins are quite distinct. Activation of phosphocholinated Rabs by GTP/GDP exchange factors (GEFs) and binding to the GDP dissociation inhibitor (GDI) are strongly inhibited, whereas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 25 publications
5
131
0
1
Order By: Relevance
“…Multiple studies have shown that phosphocholination and AMPylation of Rab1 switch II manipulate Rab1 function by blocking the ability of Rab1 to interact with GEFs and GAPs (16,28,30), because switch II serves as the primary interface for these binding events. To investigate whether phosphorylation of Rab1T75 may have a similar effect, we assayed the ability of the Legionella Rab1 GEF DrrA (GEF domain only, residues 340-533) to catalyze the displacement of mant-GDP from WT and mutant Rab1 in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that phosphocholination and AMPylation of Rab1 switch II manipulate Rab1 function by blocking the ability of Rab1 to interact with GEFs and GAPs (16,28,30), because switch II serves as the primary interface for these binding events. To investigate whether phosphorylation of Rab1T75 may have a similar effect, we assayed the ability of the Legionella Rab1 GEF DrrA (GEF domain only, residues 340-533) to catalyze the displacement of mant-GDP from WT and mutant Rab1 in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3D). DrrA 340-533 was selected for these assays as a result of numerous publications (30)(31)(32) describing similar experiments with this enzyme. We found no significant difference in the k cat /K m of DrrA 340-533 toward WT Rab1 and Rab1T75E, and only a slight difference with Rab1T75A; thus, we infer that it is unlikely phosphorylation of T75 prevents Rab1 interaction with GEFs or interferes with activation.…”
Section: Resultsmentioning
confidence: 99%
“…Automodification has been observed for most Fic proteins described to date (6,(8)(9)(10)(11)(12)(13)(14)(15). For NmFic, the sites of autoadenylylation have been mapped to Y183 and Y188 of the α inh by mass spectrometry (MS) (8) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the biological functions, as well as the molecular mechanism, of the vast majority of Fic proteins have remained elusive. Intriguingly, in vitro automodification has been demonstrated for most Fic proteins that have been described so far (6,(8)(9)(10)(11)(12)(13)(14)(15), but its physiological relevance has remained unclear.…”
mentioning
confidence: 99%
“…As in the case of adenylylation, there was a major effect on the interaction with GDI, which was essentially abolished and would therefore lead to stabilization of membrane attachment, and in this case preferentially in the inactive form due to the preference of the phosphocholination reaction for Rab : GDP. Similarly to the situation with adenylylation, L. pneumophila also secretes a protein that can reverse the modification, in this case removing the phosphocholine group hydrolytically (Tan et al, 2011;Goody et al, 2012). The similarity with adenylylation also extends to the present lack of understanding of the biological purpose of the modification, apart from the general feature that Rabs are stabilized in their membrane-bound form.…”
Section: Learning About Vesicular Transport From Bacteriamentioning
confidence: 97%